Local structure analysis of BiFeO3-BaTiO3 solid solutions. (1st November 2022) - Yoneda, Yasuhiro; Kim, Sangwook; Mori, Shigeo; Wada, Satoshi
Abstract: The average and local structures of solid solutions of (1 – x )BiFeO3 – x BaTiO3 were investigated. At room temperature, pseudo-cubic phases appear in BaTiO3 compositions with x values ranging from 0.3 to 0.7. The ferroelectricity was not lost even in the cubic structure with the highest ferroelectricity observed at x = 0.3. We used a pair distribution function and an X-ray absorption fine structure to perform a structural analysis to determine the source of this ferroelectricity. These solid solutions' local structures were consistent with the pure limits of BiFeO3 and BaTiO3, respectively, but when the composition of BaTiO3 was 0.3, a structure peculiar to the structural boundary in the solid solutions appeared. We discovered that the structure had the greatest randomness around this composition by performing a model fit of this local structure. Local structure changes to improve nanoscale dipole interactions while maintaining the ferroelectric long-range order structure. As a result, the domain size grows and the ferroelectricity improves.